Case Study : Zalynz Oven / Izyan Atasha Azman - Azman, Izyan Atasha (2020)
This case study is conducted in order to know and learn the detail of the company, Zalynz Oven that were located at Kuala Lumpur. This company mainly provided foods such as pastries, bread, cakes and spaghetti. in the first part of the case study reported, the information regarding of the company will be collected through primary or secondary source. From this source, the details of company will be get through from this. The second part of the report contains more detail regarding Zalynz Oven. Objective of the project is to work on the background, organizational structure, products description, technologies that are involved with the Zalynz Oven. From this information, we have the opportunity to learn the artificial intelligence technology used by this company, as well as business, marketing and its operational strategy to promote their product to the public. This case study also described regarding how the Zalynz Oven manage their financial as well as achievement gain from the financial management.